Disfunción eréctil y estudio vascular de arterias cavernosas como factor predictor de cardiopatía coronaria - Marconi T., Marcelo; Petricevic O., Erika; Avillo C., Víctor; Valdevenito S., Raúl; Dusaillant N., Gastón (Revista Hospital Clínico Universidad de Chile, 2009)
During the last 15 years there has been increasing evidence demonstrating that erectile dysfunction (ED) due to vascular etiology is a primary manifestation of endothelial damage and that in a high percentage of the affected men it precedes coronary artery disease (CAD). These findings have positionated ED as a significant risk factor for CAD. The association between these pathological entities relies mainly in an anatomical factor since the diameter of the cavernosal arteries is 1 to 2 mm and of the coronary arteries 3 to 4 mm. Considering that the physiopathology of the endothelial dysfunction is the same in both diseases, the clinical manifestations (DE) become apparent first in the organ with the smaller arteries. Classically the vascular study of the penis has been done with the color doppler ultrasound of the cavernosal arteries associated with an injection of prostaglandin E2; in the clinical setting this study represents a penile stress test (functional study). A pathological result in the color doppler ultrasound of the cavernosal arteries in patients with DE predicts the presence of CAD with high accuracy. Taking this information in account the specific study of these blood vessels may allow the detection of patients in risk of having CAD, positionating this study as a screnning method for patients in cardiovascular risk.